IDENTIFICATION AND CHARACTERIZATION OF A 9-CIS-HEXADECENOIC ACID CIS-TRANS ISOMERASE FROM A PSYCHROTROPHIC BACTERIUM, PSEUDOMONAS SP. STRAIN E-3 (18th Symposium on Polar Biology) - オクヤマ, ヒデトシ; エナリ, ダイスケ; モリタ, ナオキ; OKUYAMA, Hidetoshi; ENARI, Daisuke; MORITA, Naoki (National Institute of Polar Research, 1997)
P(論文) A cell-free extract of Pseudomonas sp. strain E-3 (Pseudomonas E-3) had activities that catalyzed the conversion of 9-cis-hexadecenoic acid [16:1(9c)] to 9-trans-hexadecenoic acid [16:1(9t)] in the free acid form, and when 16:1(9c) was esterified to phosphatidylethanolamine (PE). A soluble 16:1(9c) cis-trans isomerase (9-Iase) was purified to complete homogeneity from the extract of Pseudomonas E-3 and characterized. Electrophoresis on both denaturing and incompletely-denaturing polyacrylamide gels of the purified enzyme preparation showed the single band of a protein with a molecular mass of 80 kDa, suggesting that the 9-Iase is a monomeric protein of 80 kDa. The 9-Iase, assayed with 16:1(9c) as a substrate, had a specific activity of 22.8 μmol per h per mg of protein and a Km of 118 μM. The enzyme had the optimum temperature for catalysis at 30℃ and catalyzed the cis to trails conversion of a double bond of 16:1(9c) in the free acid form, but it was able to isomerize 16:1(9c) esterified to PE in the presence of the cell membrane fraction. Irrespective of the temperature at which cells of Pseudomonas E-3 were grown, the level of 16:1(9t) was around 2-4% of the total cellular fatty acids. However, when cells grown at 4℃ were warmed up to 30℃ at a rate of about 20℃/min, the level of 16:1(9t) was increased from 3% to 14%. Since the level in situ of free fatty acids in this bacterium is negligible, it is suggested that the 9-Iase is operative in vivo as the cis to trans isomerase of 16:1(9c) that is esterified to PE together with the membranous factor, and that the 9-Iase might work as a stringent modulator of membrane fluidity under abrupt alteration in growth temperature. departmental bulletin paper